Didaktik der juristischen Übersetzung in einem Online-Kurs zur Vorbereitung auf die staatliche Prüfung zum beeidigten Übersetzer der deutschen Sprache - Podlaska, Beata (Comparative Legilinguistics, 2025)
For aspiring sworn translators, translating legal texts presents a considerable challenge as it requires both terminological knowledge and an understanding of the legal systems of both language areas. This article attempts to present a method for teaching the translation of legal texts within an online course designed to prepare candidates for the state exam for sworn translators of the German language. The theoretical part details the method of teaching the translation of legal texts in the online course, which aims to impart the knowledge and skills necessary to meet the challenges that arise when translating legal texts—one of the types of texts translated in the state exam. The empirical part analyzes examples of translation errors made by aspiring translators and attempts to identify their sources.